Efeito do tanino no desempenho e características de carcaça de bovinos não castrados terminados em confinamento - Nascimento, Kaique de Souza (2019)
In order to increase the efficiency of the use of the nutrients supplied to the animals, the use of additives becomes an option because it directly interferes with the ruminal fermentation and consequently can improve the performance of the animals. Antibiotics are the most commonly used additives in feedlots, but over the years the use of antibiotic alternatives has been increasing due to the restriction of some markets to the use of antibiotics in animal production. In this sense, the use of tannins in the nutrition of beef cattle has been gaining strength as an alternative to antibiotics. The objective of this study was to evaluate the performance and carcass traits of steers in the finishing phase, receiving diets with the addition of a commercial product based on tannins or Monensina. A total of 160 Nelore (64) and Angus (96) with mean age of 20 months and initial weight of 342 ± 25 kg were used. The experimental design used was a randomized complete block, being considered as weights and breeds blocks, the experimental unit considered was the pen composed by 8 animals and 5 replicates per treatment, totaling 20 experimental units. The treatments evaluated were: M14 - Diet with 14% of CP and 25 ppm of Monensin; MT14 - Diet with 14% of CP, 25 ppm of Monensin and 0.15%/DM of Tannins; T14 - Diet with 14% of CP and 0.15%/DM of Tannins; MT13 - Diet with 13% of CP, 25 ppmof Monensin and 0.15%/DM of Tannins. The treatments provided the same diet for all animals (90 and 10%, for concentrate and forage, respectively). The experimental period was 105 days with 14 days of adaptation. The treatments MT14 and T14 presented values higher than the others for final weight (P = 0.002), dry matter intake (P <0.001), intake per live weight percentage (P <0.001), total mean gain (P = 0.005) and average daily gain (P = 0.005). Food efficiency (P = 0.157) was similar among all treatments. The parameters of ribeye area (P = 0.332), subcutaneous fat thickness (0.848), gluteus medius fat thickness (P = 0.830) and gluteus medius area (P = 0.141) obtained by ultrasonography showed no difference between the treatments. The final carcass weight (P = 0.075) and carcass ADG (P = 0.076) were higher for the MT14 and T14 treatments compared to the others. Carcass yield did not differ between treatments (P = 0.904). The use of a mixture of condensed and hydrolyzable tannins was shown to be viable in the finishing of beef cattle, presenting feed efficiency and carcass characteristics similar to the monensin additive in diets with 14% and 13% crude protein.